Measurement of the partial decay width Rb0 = Γbb/Γhad of the Z with the DELPHI detector at LEP - Abreu,P; Adam,W; Adye,T; Agasi,E; Ajinenko,I; Aleksan,R; Alekseev,GD; Alemany,R; Allport,PP; Almehed,S; Amaldi,U; Amato,S; et al. (Zeitschrift Fur Physik C Particles and Fields, 1996)
The partial decay width of the Z to bb quark pairs has been measured by the DELPHI detector at LEP. B-hadrons, containing b-quarks, were tagged by several methods using tracks with large impact parameters to the primary vertex complemented sometimes by event shape variables or using leptons with high transverse momentum relative to the hadron. In order to reduce the systematic uncertainties, in all methods the b-tagging efficiency has been extracted directly from the data. Combining all methods, the value: Γbb/Γhad = 0.2216 ± 0.0016(stat.) ± 0.0021(syst.) was found, where the cc production fraction was fixed to its Standard Model value. © Springer-Verlag 1996.